2002
DOI: 10.1007/s100380200013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the de novo regeneration of the pattern of the length heteroplasmy associated with the T16189C variant in the control (D-loop) region of mitochondrial DNA

Abstract: We have investigated the genetics of the length heteroplasmy associated with the T16189C variant of mitochondrial DNA (mtDNA), and report here definitive evidence that the pattern of the length heteroplasmy is not simply the outcome of drift related to the random segregation of the mtDNA population during cell division, but is actively maintained and regenerated de novo following each cell division. The pattern of the length heteroplasmy was maintained in a fibroblast cell line during an extensive mtDNA deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Mitochondrial DNA (mtDNA), a double‐stranded closed molecule of 16 569 base pairs (bp), encodes 37 genes (Anderson et al , ) and has non‐coding regions at displacement loop (D‐loop) region that contains three hypervariable segments (HV1, HV2 and HV3) with high polymorphism (Lutz et al , ; Imaizumi et al , ). C‐stretch is a poly C structure in mtDNA hypervariable segments caused by slipping of the DNA polymerase during replication, which is associated with sequence‐length variations (Malik et al , ; Lee et al , ; Lutz‐Bonengel et al , ). Several unique properties of mtDNA, including its high copy number, maternal inheritance, high mutation rate, and lack of recombination, have been widely accepted in the field of evolutionary relationships among human ethnic group (Wallace, ; Pakendorf and Stoneking, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA), a double‐stranded closed molecule of 16 569 base pairs (bp), encodes 37 genes (Anderson et al , ) and has non‐coding regions at displacement loop (D‐loop) region that contains three hypervariable segments (HV1, HV2 and HV3) with high polymorphism (Lutz et al , ; Imaizumi et al , ). C‐stretch is a poly C structure in mtDNA hypervariable segments caused by slipping of the DNA polymerase during replication, which is associated with sequence‐length variations (Malik et al , ; Lee et al , ; Lutz‐Bonengel et al , ). Several unique properties of mtDNA, including its high copy number, maternal inheritance, high mutation rate, and lack of recombination, have been widely accepted in the field of evolutionary relationships among human ethnic group (Wallace, ; Pakendorf and Stoneking, ).…”
Section: Introductionmentioning
confidence: 99%
“…MtDNA hypervariable segment I (HVS-I) contains a C-continuous tract termed the C-stretch, which is associated with sequence-length variations (Lee HY et al, 2004;Lutz-Bonengel et al, 2004) located in 16 180~16 193 nt. Due to slipping of the DNA polymerase during replication, the C-stretch evolves much faster than other regions of mtDNA, and variations in this region have been demonstrated widely among unrelated individuals (Malik et al, 2002a;Lee HY et al, 2004;Lutz-Bonengel et al, 2004). Furthermore, the mtDNA control region, especially the C-stretch, might be involved in the development of human diseases such as cancer (Tan et al, 2002;Lee HC et al, 2004;Meierhofer et al, 2004;Montanini et al, 2005;Sangkhathat et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As the 'out-ofphase' nucleotide pattern, C-stretch is not easily detected when compared to other regions of mtDNA, and C-stretch length heteroplasmy increases the difficulties of DNA sequencing (Lee HY et al, 2004;Lutz-Bonengel et al, 2004;Bini and Pappalardo, 2005). C-stretch is located in the middle of mtDNA HVS-I, and failure to interpret these sequence variations may hinder the application of the mtDNA control region to forensic and population genetics (Malik et al, 2002a;Lee HY et al, 2004). Therefore, the C-stretch might be highly significant in forensic identification and population genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that cisplatin may have directly attacked the longer poly-C tracts of mtDNA and inhibited their replication, resulting in the selection of shorter poly-C tracts. Although it was reported that the pattern of the OriB poly-C length heteroplasmy in sister cells that had been produced by replication slippage were similar33, cells harbouring the shorter pattern may be present at very low frequency. Such cells might be selected as the resistant cells during the treatment of cisplatin.…”
Section: Discussionmentioning
confidence: 95%